2006
DOI: 10.1016/j.ygeno.2005.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Human mitochondrial pyrophosphatase: cDNA cloning and analysis of the gene in patients with mtDNA depletion syndromes

Abstract: Pyrophosphatases (PPases) catalyze the hydrolysis of inorganic pyrophosphate generated in several cellular enzymatic reactions. A novel human pyrophosphatase cDNA encoding a 334-amino-acid protein approximately 60% identical to the previously identified human cytosolic PPase was cloned and characterized. The novel enzyme, named PPase-2, was enzymatically active and catalyzed hydrolysis of pyrophosphate at a rate similar to that of the previously identified PPase-1. A functional mitochondrial import signal sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Taken together, these data underscore that MPTP-induced mitochondrial complex I dysfunction can lead to alterations in the levels of other components of the respiratory chain, in analogy to what occurs in PD [6,75,80] and other neurodegenerative diseases affecting the brain and/or the retina. In a related fashion, an additional enzyme whose levels we have found decreased in the parkinsonian monkey retina is inorganic pyrophosphatase 1 (PPA1), which is responsible for modulating Pi levels and is intimately linked to cell survival [81,82]. Given that its activity is coupled to reactions in which PPi is released, and that it provides a thermodynamic pull for many biosynthetic reactions, its lower levels found in our experimental system are consistent with a situation in which the production of ATP is decreased due to the MPTP-provoked mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data underscore that MPTP-induced mitochondrial complex I dysfunction can lead to alterations in the levels of other components of the respiratory chain, in analogy to what occurs in PD [6,75,80] and other neurodegenerative diseases affecting the brain and/or the retina. In a related fashion, an additional enzyme whose levels we have found decreased in the parkinsonian monkey retina is inorganic pyrophosphatase 1 (PPA1), which is responsible for modulating Pi levels and is intimately linked to cell survival [81,82]. Given that its activity is coupled to reactions in which PPi is released, and that it provides a thermodynamic pull for many biosynthetic reactions, its lower levels found in our experimental system are consistent with a situation in which the production of ATP is decreased due to the MPTP-provoked mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, XP_660572.1 (spot 1180; homologous to A. fumigatus Af293 inorganic diphosphatase BLASTP E = 4 · 10 À150 and Schizosaccharomyces pombe PPA1 BLASTP E = 2 · 10 À123 ) may be involved in phosphate turnover. PPA1 is a cytoplasmic enzyme that is essential for growth (Kolakowski et al, 1988;Lundin et al, 1991) and is required for the hydrolysis of inorganic pyrophosphate to two molecules of orthophosphates (Curbo et al, 2006;Lundin et al, 1991). Thus XP_660572.1's increased expression in osmoadapted cells imply a faster turnover of phosphates to be utilized in other cellular signaling pathways that require phosphorylation (Hohmann, 2002).…”
Section: General Stress Response Proteins Involved In Protein Turnovermentioning
confidence: 99%
“…Other organelles, such as mitochondria and peroxisomes, remain active much longer and provide energy for the cell as well as take over a number of metabolic tasks during this process (Keech et al, 2007;Chrobok et al, 2016). While yeast and animals possess mitochondrial PPases (Lundin et al, 1991;Curbo et al, 2006), so far no mitochondrial PPase has been identified in plants. But generally PPases remove pyrophosphate (PP i ) that is created as a byproduct of anabolic processes such as nucleic acid, protein, and carbohydrate synthesis (Gómez-García et al, 2006).…”
mentioning
confidence: 99%